İNEK SÜTÜ ALERJISI TANISI KONULAN ÇOCUKLARDA KEÇI VE KOYUN SÜTÜ ARASINDAKI ÇAPRAZ DUYARLILIĞIN VE ISITILMIŞ SÜT ÜRÜNLERINE KLINIK REAKTIVITENIN DEĞERLENDIRILMESI - ÇİLKOL, LÜTFİYE (Fırat Üniveristesi, 2015)
İnek sütü alerjisi süt çocukluğu döneminde en sık görülen besin alerjisidir. İlk iki yaşta inek sütü alerjisi sıklığı %2-3 civarındadır. Günümüzde inek sütü alerjisi diğer besinlerle kıyaslandığında görülme sıklığı giderek artış göstermektedir. Bu nedenle inek sütü alerjisi olan hastaların takibi çok önemlidir. Çalışmamızda inek sütü alerjisi olan hastaların inek sütü yerine koyun, keçi sütünü ve farklı inek sütü formu olan fırınlanmış süt ürünlerini kullanıp kullanamayacağının belirlenmesi amaçlandı. Çalışmaya yaşları 0-4 yaş arası 40 inek sütü alerjisi olan hasta ve 40 sağlıklı kontrol grubu alınmıştır. Bu hastalarda vitamin D düzeyi çalışılarak inek sütü alerjisi olan hastalar ile sağlıklı çocuklar arasında serum vitamin D düzeyinde anlamlı bir farklılık bulunmamıştır. İnek sütü alerjisi olan hastaların tamamında koyun sütü alerjisi olduğu, %10 hastada keçi sütü alerjisi olmadığı bulunmuştur. Fırınlanmış süt ürünlerini %62,5 hasta tolere etmiş olup bu hastalarda kazein spesifik IgE için kesim noktası 4,08 kU/L olarak saptanmıştır. Fırınlanmış süt ürünlerini tolere eden ve edemeyen hastalar arasında inek sütü deri testi, inek sütü, koyun sütü, keçi sütü prick to prick testi, inek sütü, koyun sütü, keçi sütü, alfalaktalbumin, betalaktoglobulin, kazein spesifik IgE, vitamin D düzeylerinde anlamlı farklılık bulunmamıştır. Anamnezde ve prediktif değerin altında olan hastalara yapılan inek sütü yüklemede anaflaksi gelişen hastaların inek sütü deri testi, inek sütü, koyun sütü, keçi sütü prick to prick testi, inek sütü, koyun sütü, keçi sütü, alfalaktalbumin, betalaktoglobulin, kazein spesifik IgE, vitamin D düzeylerinin anaflaksi gelişmeyen hastalara göre anlamlı olarak farklı olmadığı görülmüştür. Daha geniş hasta grupları ile yapılacak çalışmalar, inek sütü alerjisi olan hastalarda fırınlanmış süt ürünlerinin immunoterapi aracı olarak kullanılarak takipte bu hastaların inek sütüne daha çabuk tolerans geliştirdiğinin görülmesini sağlayacaktır. Anahtar Kelimeler: İnek sütü, keçi sütü, koyun sütü, ısıtılmış süt ürünü

Allergy to cow milk is the most commonly encountered food allergy among infants. During the first two years of life, the incidence of cow milk allergy is approximately 2-3%; however, the incidence of cow milk allergy is gradually increasing compared to other food allergies. For this reason, it is important to closely follow and monitor patients who have allergy to cow milk. The aim of this study was to investigate whether patients with cow milk allergy can instead consume sheep milk, goat milk, or baked cow milk products (which is cow milk presented in a different form). The study was performed on 40 patients with allergy to cow milk (the study group) and 40 healthy controls (the control group) between the ages of 0 and 4. Vitamin D levels were assessed in these patients and healthy controls, and no significant difference was identified between the two groups with respect to their serum vitamin D levels. All of the patients with allergy to cow milk also exhibited allergy to sheep milk, while only 10% lacked allergy to goat milk. Baked milk products were tolerated by 62.5% of the patients, and the breakpoint for casein-specific IgE was determined as 4.08 kU/L for these patients. No significant differences were identified between patients who were tolerant and those who were not tolerant of baked cow milk products with respect to their cow milk skin tests; their cow milk, sheep milk and goat milk skin prick to prick tests; and their cow milk, sheep milk and goat milk alpha-lactalbumin, beta-lactoglobulin, casein-specific IgE and vitamin D levels. Patients who developed anaphylaxis in their medical history or during administering cow milk who had values below predictive levels and patients who did not develop anaphylaxis it was observed that there were no significant different between these patients terms of their cow milk skin tests; their cow milk, sheep milk and goat milk skin prick to prick tests; and their cow milk, sheep milk and goat milk alpha-lactalbumin, beta-lactoglobulin, casein-specific IgE and vitamin D levels.. Further studies with larger patient groups will help demonstrate that baked cow milk products can be used as immunotherapy agents for patients with cow milk allergy, allowing them to rapidly develop tolerance to cow milk. Keywords: Cow's milk, goat 's milk, sheep 's milk, heated milk products
The evaluation of cross-sensitivity to goat and sheep milk, and of the clinical reactivity to heated milk products, in children diagnosed with cow milk allergy
Keywords: Çocuk Sağlığı ve Hastalıkları